Gender gaps in the path to adulthood for young females and males in six African countries from the 1990s to the 2010s - Jane Kabubo-Mariara; Andy McKay; Andy Newell; Cinzia Rienzo (IZA Journal of Development and Migration, 2018)
In this paper, we study on a comparative basis the school-to-work transition of young women and young men in six countries in sub-Saharan Africa, and we examine how this has evolved over recent years, based on the data collected by Demographic and Health Surveys. We examine educational attainments and the nature of early jobs young people are able to obtain, as well as considering their relationship to marriage and fertility outcomes, factors which are likely to be particularly relevant for young women. A pooled regression analysis shows that educational levels have increased substantially and gender gaps have narrowed in most countries. Access to better jobs has improved much more slowly with unchanging gender gaps in most countries, so that agriculture is still the dominant sector of employment for most young men and women. We model correlates of key educational outcomes and access to different types of jobs those controlling for individual- and household-level characteristics, including marital status, presence of children and wealth. Attaining a high level of education is unsurprisingly critical for access to the best jobs and is also associated with young women delaying marriage and childbearing.
Keywords: I21; J21; J24; O55; 330; First job; Education; School-to-work transition; Sub-Saharan Africa